Pesantren Management Based on the Entrepreneurial Eco-Theology Model: Strategies for Achieving the SDGs Through Sustainable Business Innovation - Elim Halimatusadiyah; Yupi Pirdayanti; Wiwin Nurjamilah (DAAR EL-IDARAH: Journal of Islamic Education Management, 2025)
This systematic literature review explores the integration of pesantren management with an entrepreneur eco-theology model as an innovative strategy to realize the Sustainable Development Goals (SDGs). By combining Islamic environmental ethics, pesantren education, and sustainable business innovation, this model offers a holistic approach to development that balances economic growth, environmental sustainability, and social justice. Based on an analysis of 116 scholarly articles, this study synthesizes five key pillars: Islamic eco-theology, pesantren-based conservation, sustainable social entrepreneurship, Islamic finance integration, and green strategy implementation (such as precision agriculture and circular economy). The synthesis confirms that pesantrens hold a strategic position as agents of ecological change through the moral authority of kyais, santri social capital, and economic independence. Real-world practices from pesantrens such as Biharul Ulum Agroecology and ath-Taariq demonstrate that environmental theology transformed into sustainable business actions can mitigate environmental crises.while alleviating poverty. This review yields an integrative conceptual framework and recommends integrated curriculum development and pesantren business incubators as practical guidance for policymakers.